PERTANGGUNGJAWABAN KEUANGAN NEGARA PADA AKHIR DAN SETELAH TAHUN ANGGARAN BERJALAN - Raya, Muhammad Yaasiin (El-Iqthisadi, 2019)
Abstract Accountability for the current fiscal year is based on principles that are in line with the principles of good governance. These principles are set forth through the application of classical principles and new principles in the accountability of state finances. Accountability of state finances at the end of the fiscal year that carries out responsibility is the head of the office or agency to superiors and to higher officials. Accountability of the State finances after the end of the fiscal year that is accountability through the judicial institution, namely the existence of state financial losses that must be accounted for in the relevant court, namely the court of corruption in the general court handling cases of state losses. Keywords: Accountability, Budget, State Finance. Abstrak Pertanggungjawaban keuangan negara tahun anggaran berjalan didasarkan atas prinsip-prinsip yang sejalan dengan prinsip-prinsip good governance. Prinsip-prinsip tersebut dituangkan melalui penerapan asas-asas klasik maupun asas-asas baru dalam pertanggungjawaban keuangan negara. Pertanggungjawaban keuangan negara pada akhir tahun anggaran itu yang melakukan pertanggungjawaban yaitu kepala kantor atau instansi kepada atasan dan kepada pejabat yang lebih tinggi. Pertanggungjawaban keuangan Negara setelah akhir tahun anggaran yaitu pertanggungjawaban dengan cara melalui lembaga peradilan, yaitu adanya kerugian keuangan Negara yang harus di pertanggungjawaban di pengadilan yang bersangkutan yaitu pengadilan tindak pidana korupsi pada pengadilan umum yang menangani kasus kerugian negara. Kata Kunci : Anggaran, Keuangan Negara, Pertanggungjawaban.